KONTRIBUSI DAN PENAWARAN TENAGA KERJA ANGGOTA RUMAH TANGGA PEKEBUN KELAPA SAWIT : Kasus di Desa Sri Kuncoro Kecamatan Pondok Kelapa Kabupaten Bengkulu Utara - Ketut Sukiyono; Sriyoto Sriyoto (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2005)
This research was aimed to investigate contribution of labour and various factor influencing household labour supply. Multiple linear regresion model estimated by Ordinary Least Square was used. Twenty nine palm oil estate households in Sri Kuncoro were censused and interviewed to get primary data. The research found that husband contribution at plantation activities was the biggest compared to his wife, children and other family members. Further, elatif estate wage to agricultural wage and the existence of othe family members were significant factors to influence household labour supply while respondent age, education level, palm tree age, and relatif estate wage rate to non agricultural wage rate were not.